Faktor-Faktor yang Berhubungan dengan Kejadian Abortus pada Ibu Hamil di Poli Kebidanan Rs Budi Kemuliaan Batam - Sukma Sahreni; Dino Gagah,P; Fikri Septian (Universitas Batam, 2022)
Background: Abortion is still a big problem in Indonesia in terms of epidemiology, morbidity, mortality, and prognosis. The unclear pathogenesis due to the uncertainty of etiology and risk factors is reflected in research design with a case control approach. The sampling technique used is purposive sampling with a sample of 69 people. Sources of data used in this study is medical records. Data analysis using Chi Square statistical test. Method : This study uses an analytical observational research design with a case control approach. The sampling technique used is purposive sampling with a sample of 69 people. Sources of data used in this study is medical records. Data analysis using Chi Square statistical test. Results: From the results of the study, it was found that parity, maternal age, and iron deficiency anemia had a relationship with the incidence of abortion, while a history of abortion had no relationship with the incidence of abortion. The results of the Chi Square statistical test showed that the p-value for parity was 0,000, maternal age was 0,000, history of abortion was 0,779, and iron deficiency anemia was 0,007. Conclusion: Based on the results of data processing, it can be concluded that there is a significant relationship between parity, maternal age, and iron deficiency anemia with the incidence of abortion and there is no significant relationship between the history of abortion and the incidence of abortion at the obstetrics poly at Budi Kemuliaan Hospital Batam.